A survey of macroinvertebrates colonizing bluehead chub nests in a Virginia stream. Issue 1 (2nd January 2016) - Swartwout, Meredith C.; Keating, Fiona; Frimpong, Emmanuel A.
Abstract : Chubs of the genus Nocomis build large pebble nests that may serve as an important microhabitat for macroinvertebrates and small vertebrates in streams of eastern North America. Macroinvertebrates that use chub nests have not been systematically documented. In this study, we examined the macroinvertebrate communities present inside bluehead chub Nocomis leptocephalus nests in a small tributary creek of the New River in Virginia, USA. Individuals from 38 families of macroinvertebrates were recovered from nests. Snails from the family Pleuroceridae were the most numerous invertebrates in four nests examined, making up an average of 13.6 ± 7.53% of the macroinvertebrate community. This study revealed that communities in chub nests are diverse but not necessarily unique from the surrounding stream substrate. More long-term studies on macroinvertebrate communities of chub nests are needed to elucidate the function of nests as a stream microhabitat.